2018
DOI: 10.1088/1748-9326/aaf07b
|View full text |Cite
|
Sign up to set email alerts
|

Response of electricity sector air pollution emissions to drought conditions in the western United States

Abstract: Water is needed for hydroelectric generation and to cool thermoelectric power plants. This dependence on water makes electricity generation vulnerable to droughts. Furthermore, because power sector CO 2 emissions amount to approximately one third of total US emissions, droughts could influence the interannual variability of state-and national-scale emissions. However, the magnitude of drought-induced changes in power sector emissions is not well understood, especially in the context of climate mitigation polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…In the last few decades, drought cycles have become more intense and frequent all over the world due to rapid climate change [9,[68][69][70]; for instance, in Brazil [71], Syria [63], Hungary [52], China [72], and southern Europe [73]. Subsequently, many industries have been affected either directly or indirectly, such as the agricultural sector [74][75][76][77][78][79], hydrology [80][81][82][83], the economy [76,84], human health [85][86][87], and tourism [88][89][90]. In this sense, our research shows a negative trend in agricultural drought episodes across Hungarian counties (Figure 4; Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, drought cycles have become more intense and frequent all over the world due to rapid climate change [9,[68][69][70]; for instance, in Brazil [71], Syria [63], Hungary [52], China [72], and southern Europe [73]. Subsequently, many industries have been affected either directly or indirectly, such as the agricultural sector [74][75][76][77][78][79], hydrology [80][81][82][83], the economy [76,84], human health [85][86][87], and tourism [88][89][90]. In this sense, our research shows a negative trend in agricultural drought episodes across Hungarian counties (Figure 4; Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sectoral studies are informative but can miss important indirect impacts that occur across sectors through intersectoral linkages (O'Brien et al., ). There has been a growing body of research taking more integrated approaches to examine the impacts of climate change beyond the direct (Calvin & Fisher‐Vanden, ; Herrera‐Estrada, Diffenbaugh, Wagner, Craft, & Sheffield, ; Nicholls & Kebede, ; Nkhonjera & Dinka, ; Smithers & Blicharska, ). But substantial knowledge gaps remain (Melillo et al., ).…”
Section: Toward a Better Understanding Of Climate Change Impactsmentioning
confidence: 99%
“…The , 2006). There has been a growing body of research taking more integrated approaches to examine the impacts of climate change beyond the direct (Calvin & Fisher-Vanden, 2017;Herrera-Estrada, Diffenbaugh, Wagner, Craft, & Sheffield, 2018;Nicholls & Kebede, 2012;Nkhonjera & Dinka, 2017;Smithers & Blicharska, 2016). But substantial knowledge gaps remain (Melillo et al, 2014).…”
Section: Ie Models To Estimate Climate Change Impactsmentioning
confidence: 99%
“…HP reduction due to drought is particularly problematic in countries that strongly rely on hydropower for their electricity supply, which include many countries in Africa and South America (EIA, 2019). For the western United States, it was found that frequent droughts had caused a notable shift toward conventional energy sources, thus leading to increases in air pollutant emissions of around 10% (Herrera‐Estrada et al., 2018).…”
Section: Introductionmentioning
confidence: 99%